PERANCANGAN SISTEM INFORMASI KONSULTASI PENCEGAHAN DAN PENANGANAN STUNTING BALITA BERBASIS WEBSITE PADA POSYANDU MERPATI B - Jou Ezekiel (2023)
The main cause of stunting is child malnutrition during the first 1,000 days of life (HPK), this is the critical period for toddlers. Assessment of the nutritional status of toddlers is based on length and height according to age. Merpati B Posyandu located in Cikumpa Village RT/RW.002/010, Sukmajaya District, Depok City still uses manual data processing and stunting consultations, namely using paper as a medium for recording data and having to wait for the posyandu to be able to carry out consultations on stunting problems. Based on problems that exist at Posyandu Merpati B, to strengthen health services, and simplify posyandu data processing, it is necessary to design an information system that can provide an efficient and effective system. The method used in designing information systems is the Waterfall method. This Waterfall method will make the information system design flow process orderly and structured in each process. This research produces a website-based information system that can process data, display data on toddlers, and information regarding prevention and treatment efforts, as well as consultations with health workers.